Hcbs Service Intensity and Nursing Home Placement for Patients with Alzheimer's Disease and Related Dementias: Does Race Matter?. (20th August 2020) - Yan, D.; Wang, S.; Temkin‐Greener, H.; Cai, S.
Abstract : Research Objective: To explore racial differences in the nursing home (NH) placement among Medicare‐Medicaid dual‐eligible home and community‐based service (HCBS) users with Alzheimer's disease and related dementias (ADRD), and determine the extent to which HCBS generosity may be influential. Study Design: The following 2010‐2013 national data were linked at the individual level: Medicaid Analytic eXtract (MAX) Personal Summary (PS) file and Other Therapy (OT) file, the Minimum Data Set (MDS) 2.0/3.0 and Medicare Beneficiary Summary File and MedPAR. Dually eligible fee‐for‐service Medicare and Medicaid beneficiaries were identified using MBSF. Diagnosis of ADRD was based on the MBSF chronic condition file. New users were defined as those who did not have HCBS episodes in a prior 30‐day look‐back period, based on the OT records. The outcome variable was any NH admission within one year after the HBCS use, defined based on the MDS data. The main variables of interest were race (ie, white, black, other), the intensity of HCBS among ADRD population at the county level (the average monthly spending per HCBS user with ADRD in a county, based on MAX PS file), and the interaction terms between the intensity of ADRD and race. A linear probability model with county fixed‐effect and robust standard errors were estimated, accounting for individual covariates (eg, demographic characteristics, chronic conditions, prior use of institutional care). Population Studied: 1 527 974 new users of HCBS with ADRD during CY2010 to 2013. Principal Findings: The intensity of HCBS among individuals with ADRD varies widely across counties, the 25th percentile, median, and the 75th percentile was 654, 827, and 1099, respectively. The overall NH admission rate among HCBS users with ADRD was 67%, 55%, and 36% for whites, blacks, and others, respectively. After accounting for individual covariates, whites continued to exhibit a higher NH admission rate, as compared with two other race groups. However, while a higher intensity of HCBS reduced the likelihood of NH placement for whites, it increased the risk among blacks. NH admission rate for blacks was 7.2 percentage points ( P < 0.01) lower than for whites in a county with a median HCBS monthly spending. A one hundred dollars increase in monthly HCBS spending was associated with a 0.3 percentage points ( P < 0.01) decrease in admission rate among whites, but a 0.3 percentage points ( P < 0.01) increase among blacks. Conclusions: Our findings suggest that among dual‐eligible HCBS users with ADRD, whites were more likely to have NH admission within 1 year than non‐whites. Moreover, higher intensity of HCBS in a county was associated with lower a NH admission rate among whites, but a higher rate among blacks. Implications for Policy or Practice: States have been promoting the use of HCBS as the means of rebalancing the cost of traditional institutional care while allowing more people to remain living in the community. However, the expansion of HCBS may have differential impact on NH admission risk for whites and blacks. Better understanding of racial differences in care needs is critical to inform the State Medicaid program design. Primary Funding Source: National Institutes of Health.